Effects of two exercise programs on health-related fitness, quality of life and exercise enjoyment in adults with visual impairment: a randomized crossover trial - Rafael B. P. da Silva; Eduardo L Caputo; Natan Feter; Felipe F Reichert (BMC, 2022)
Abstract Background So far there is no study comparing two distinct exercise interventions in people with visual impairment. This study aimed to evaluate the effects of two exercise programs on health-related fitness, quality of life, and exercise enjoyment in people with visual impairment. Methods Two exercise interventions were conducted: sports (i.e., Goalball, Football 5-a-side and Martial Arts) and functional training (i.e., Bodyweight exercises). Physical fitness was assessed by handgrip strength, flexibility, abdominal endurance, and cardiorespiratory fitness. The Physical Activity Enjoyment Scale (PACES) measured the pleasure in the practice of physical exercises, and the quality of life was measured by the WHOQOL-Bref. Results A significant time x group interaction terms were observed for flexibility (P < 0.001; Cohen d = 0.08), abdominal muscular endurance (P < 0.001; Cohen d = 0.15), and distance covered in the 6-min walk/run test (P = 0.018; Cohen d = 0.02). An improvement of 13.3% and 5.1% on the distance covered on the 6-min walk/run test after sports and functional training was also observed. Conclusion The functional training program was reported as more pleasant for participants. Sports-related exercises and functional training improved health-related fitness and quality of life for people with visual impairment.